Cultural Code in the Serat Pasindhen Bedhaya Mintaraga Yasan Dalem of Sri Sultan Hamengku Bawono Ka-10 - Raihan Adib Ghifari; Rahma Ari Widihastuti; Yusro Edy Nugroho; Rajeev Kumar (Sutasoma : Jurnal Sastra Jawa, 2026)
Bedhaya is a dance performed by female dancers within the royal palace environment. One of the Bedhaya dances preserved in the Karaton Ngayogyakarta Hadiningrat is Bedhaya Mintaraga, the yasan dalem of Sri Sultan Hamengku Bawono Ka-10. Bedhaya Mintaraga conveys messages about the noble values a ksatria must possess, represented by Raden Arjuna during his ascetic period, titled Begawan Mintaraga. These messages are conveyed not only through dance movements but also through the Serat Pasindhen sung by the sindhen. In this context, A.Teeuw’s semiotic theory, particularly cultural codes, is used to examine how cultural codes in the Bedhaya Mintaraga represent and transmit life values through artistic symbols. The results of the study show that the cultural code in the Serat Pasindhen Bedhaya Mintaraga reflects the social practices in the Karaton Ngayogyakarta Hadiningrat environment, when the Serat Pasindhen Bedhaya Mintaraga includes the concept of babahan hawa sanga, forms of symbolic legitimization, representations of prayer, and the figure of Raden Arjuna, as well as life teachings that emphasize the principle of memayu hayuning Buwono. This research shows that the performing arts of the Karaton Ngayogyakarta Hadiningrat can be understood as a cultural text that serves to preserve philosophical teachings and strengthen cultural identities, both of which remain relevant to society.